Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 154021 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Mammalia", "Geometry POLYGON((-81.76 -3.14,-81.76 14.24,-54.21 14.24,-54.21 -3.14,-81.76 -3.14))", "HasGeospatialIssue is false" ] } The dataset includes 154021 records from 99 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0051183-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences